Hair Dyeing Ingredients in The Sight of The Prophetic Hadith - Wulandari Agustina; Muhajirin; Nadhiran, Hedhri (CV. Doki Course and Training, 2024)
This article aims to discuss hair dye ingredients from the perspective of the Prophet's hadith. Hair color was chosen as the object of study because it has now become a trend and was exemplified by the Prophet. Additionally, hair color has become an important part of a person's style, pattern and everyday appearance, in addition to clothing design. It's not just the haircut that changes, there are also various types of materials used to vary the hair. By using descriptive-analytical qualitative methods, this article concludes that a search of the Prophet's hadiths relating to hair dyes shows that the Prophet used hair colors made from henna and katam. However, there is no prohibition against the use of other than henna dye and katam (manufactured hair dye), but their use should not be excessive and should not be used for a long period of time, because these ingredients contain dangerous ingredients that can cause different diseases- different. Thus, this article can be used as a guide for Muslims to color their hair according to their needs, referring to developments and demands of the times.